The Status of Computer Assisted School Administration and Strategies for its Further Development in Negeri Sembilan Secondary Schools - Liong, Kam Chong (1994)
The tangible advantages of computer use in terms of efficiency and effectiveness have led to an increasing number of schools in Malaysia using computers in administration. Schools, however, are only working on their own initiative. There is as yet no central support or policy for computer assisted school administration (CASA). Experiences in countries more advanced in CASA development almost invariably attest that if schools are left to venture on their own, they are most unlikely to reap the full benefits of CASA . The need for definite strategies for CASA development is apparent. This study presents a descriptive account of the extent of school administrative computing in secondary schools in the state of Negeri Sembilan. In addition, school principals' perception of factors regarded as important for implementing school administrative computing were sought. These findings, together with insights gained from relevant literature reviews on CASA implementation successes in other countries, formed the basis for recommending strategies for further development of CASA in secondary schools in Negeri Sembilan. Such strategies should also be of relevance to other states as well as to CASA development nationwide.The data were gathered by a survey questionnaire sent to all secondary schools in Negeri sembilan and also through visits and interview sessions conducted in four selected schools. A descriptive account of the computer installations and applications used is given. Also, the relationships that exist between the five "blocks" as depicted in Visscher' s Framework for Analysis of School Information System is discussed in the context of CASA development in Negeri sembilan secondary schools. These "blocks" refer to five aspects of a school information system viz. design and development, quality, use, other factors affecting use and impact of use.